Stress granules: stress-induced cytoplasmic mRNPs compartments linked to mRNA translational regulatory pathways - Adjibade, Pauline; Mazroui, Rachid (Frontiers in RNA Research, 2023)
Stress granules (SG) are macro-complexes that assemble as phase-separated and dynamic RNA biocondensates in the cytoplasm of the eukaryotic cell when the initiation step of the general translation of mRNAs is stalled. This occurs mainly as an adaptive cell response to either environmental (i.e., radiation, exposure to chemical drugs), pathological (i.e., viral treatment), physiological (i.e., oxygen-, amino acids-, and glucose-deprivation), or therapeutic (i.e., treatment with anti-cancer drugs) translational stress. SG also formed when translation initiation is blocked through stress-independent events including alteration of the activities of specific translation initiation factors and RNA-binding proteins. Both stress-dependent and –independent inhibition of translation initiation results in the accumulation of untranslated mRNAs, considered as integral components of SG. Consistently, in vivo assays of SG assembly combined with in vitro-based assembly of SG-like biocondensates studies support a fundamental role of the accumulation of untranslated mRNA in initiating the formation of SG, which then further promote their repression, potentially in a feed-back regulatory mechanism. The potential role of SG in actively repressing translation of associated mRNAs has been supported by a number of functional studies, establishing SG as critical regulatory sites of RNA homeostasis, in particular during stress. The view that the SG environment restricts translation of associated mRNAs was however challenged in studies showing that stress-induced translation repression can occur similarly in absence and presence SG, leading to the emerging concept that formation of SG and translation repression are uncoupled processes. While it still a debate if mRNA recruitment to SG contributes to their translation repression, recent finding reported translation of reporter mRNAs in SG, suggesting rather an active translational role of SG. In this review, we describe the main translational signaling pathways that regulate the biology of SG, summarize current data supporting RNA as an integral functional component of SG, and then discuss evidence supporting or not the role of SG in regulating translation either negatively or positively during stress.